Corporations' use and misuse of evidence to influence health policy: a case study of sugar-sweetened beverage taxation - Gary Jonas Fooks; Simon Williams; Graham Box; Gary Sacks (BMC, 2019)
Abstract Background Sugar sweetened beverages (SSB) are a major source of sugar in the diet. Although trends in consumption vary across regions, in many countries, particularly LMICs, their consumption continues to increase. In response, a growing number of governments have introduced a tax on SSBs. SSB manufacturers have opposed such taxes, disputing the role that SSBs play in diet-related diseases and the effectiveness of SSB taxation, and alleging major economic impacts. Given the importance of evidence to effective regulation of products harmful to human health, we scrutinised industry submissions to the South African government's consultation on a proposed SSB tax and examined their use of evidence. Results Corporate submissions were underpinned by several strategies involving the misrepresentation of evidence. First, references were used in a misleading way, providing false support for key claims. Second, raw data, which represented a pliable, alternative evidence base to peer reviewed studies, was misused to dispute both the premise of targeting sugar for special attention and the impact of SSB taxes on SSB consumption. Third, purposively selected evidence was used in conjunction with other techniques, such as selective quoting from studies and omitting important qualifying information, to promote an alternative evidential narrative to that supported by the weight of peer-reviewed research. Fourth, a range of mutually enforcing techniques that inflated the effects of SSB taxation on jobs, public revenue generation, and gross domestic product, was used to exaggerate the economic impact of the tax. This "hyperbolic accounting" included rounding up figures in original sources, double counting, and skipping steps in economic modelling. Conclusions Our research raises fundamental questions concerning the bona fides of industry information in the context of government efforts to combat diet-related diseases. The beverage industry's claims against SSB taxation rest on a complex interplay of techniques, that appear to be grounded in evidence, but which do not observe widely accepted approaches to the use of either scientific or economic evidence. These techniques are similar, but not identical, to those used by tobacco companies and highlight the problems of introducing evidence-based policies aimed at managing the market environment for unhealthful commodities.